Exploration of alcohol dehydrogenase EutG from Bacillus tropicus as an eco-friendly approach for the degradation of polycyclic aromatic compounds - Muhammad Naveed; Fatima Iqbal; Tariq Aziz; Ayesha Saleem; Tayyab Javed; Mahrukh Afzal; Muhammad Waseem; Metab Alharbi; Thamer H. Albekairi (Scientific Reports)
Abstract Polycyclic aromatic compounds (PACs) are pervasive environmental contaminants derived from diverse sources including pyrogenic (e.g., combustion processes), petrogenic (e.g., crude oil), and biological origins. They are commonly found in gasoline, coal, and crude oil, reflecting their prevalence and varied origins in natural and anthropogenic activities. The aim of this study is to use Bacillus tropicus which is a spore-forming, gram-positive and facultative anaerobic bacteria, containing a gene for PACs degradtion. In this study bacterial sample was collected from women’s vaginal discharge through streaking and spreading techniques. The DNA was extracted from bacterial culture and then the bacterium was identified through 16S rRNA which appeared to be B.tropicus. Then the computational analysis was conducted where the sequence similarity and functional analysis of alcohol dehydrogenase EutG protein from B.tropicus was analyzed through PSI-BLAT and SMART tool, respectively. The PSI-BLAST showed 100% query coverage score and 9 domains of alcohol dehydrogenase EutG protein were predicted through SMART tool. The quality of the protein was also assessed through ProQ server with a predicted LQ score of 8.091, a Maxsub score of − 0.350 and a z score of − 10.76. Then the phylogentic analysis was conducted to know the evolutionary relationship and closely related taxa. The 3D structure of the protein was predicted through SWISS MODEL and its quality was predicted through ERRAT with overall qauality factor of 98.708. The Ramachandran plot also predicted its quality and showed that 93.8% residues were in the most favored region. After this, 3D stucture of PACs were obtained from PubChem and molecular docking of the protein was performed with each of the compound. The lowest energy of − 10.3 was obtained with Indeno[1,2,3-cd] pyrene and the best docked complex was visulaized through discover studio to analyze its binding residues. Lastly, in-silico site-directed mutagenesis studies were performed which showed that the EutG gene (codes for alcoholic dehydrogenase) obtained from B. tropicus, will not get altered or have any decreasing effect on the enzyme’s stability if it goes through any mutations. This suggests that B. tropicus can act as an efficient, non-virulent, and reliable candidate for the eco-friendly and cost-effective bioremediation of PACs.